Effect of zinc chloride added to self-etching primer on bond strength to caries-affected dentin and chemical-physical-mechanical properties of adhesives - Campos, R. M.P. (2019)
The aim of this in vitro study was to evaluate the effect over time of zinc chloride (ZnCl2) incorporated into the primer of a two-step self-etching adhesive system (Clearfil SE Bond, Kuraray - SE) on long-term microtensile bond strength (μTBS) to caries-affected dentin (CAD), and on flexural strength (FS) and conversion degree (CD) of the adhesive. First, the CD of SE with and without 2% (wt) ZnCl2 solution was evaluated by Fourier transform infrared spectroscopy (FTIR). Then, beam-shaped samples (7 mm × 2 mm x 1 mm) were prepared with the SE primer containing the ZnCl2 solution, to perform flexural strength (FS) tests. For μTBS testing purposes, CAD surfaces were randomly divided into two groups, according to the presence of ZnCl2 powder (2 wt%) incorporated into the adhesive system (ZnCl2), or its absence (NT). An additional group consisting of dentin pretreated with a 2% chlorhexidine digluconate (CHX) solution was proposed as a positive control (n = 10). A two-step self-etching system (SE) was applied following the manufacturer's instructions, and restorations of composite resin were built up on the dentin. After 24 h, the resin-dentin blocks were sectioned into specimens that were submitted to μTBS testing immediately following, or after 12 months of water storage (WS). Both μTBS and FS tests were performed using a universal testing machine (0.5 mm/min). FS and CD data were submitted to the Student t-test, and μTBS data were submitted to two-way ANOVA and Tukey's test (α = 0.05). ZnCl2 incorporation had no statistically significant influence on flexural strength (p = 0.88) or conversion degree (p = 566). Regarding μTBS, no significant effect of the double interaction of “dentin treatment” versus “WS period” (p = 0.546) was observed. The bond strength was not affected by the WS period (p = 0.805). The highest mean bond strength was observed for the NT group, which did not differ from the ZnCl2 group. The lowest mean bond strength was observed for the CHX group, which differed statistically from the NT group (p = 0.053). It was concluded that incorporation of ZnCl2 into the SE self-etching primer did not interfere in the bond strength of caries-affected dentin, in regard to failure mode, flexural strength or CD, and had no other beneficial effects.